Pathogenicity of the diffusely adhering strain Escherichia coli C1845: F1845 adhesin-decay accelerating factor interaction, brush border microvillus injury, and actin disassembly in cultured human intestinal epithelial cells. - Bernet-Camard, M F (1996)
The diffusely adhering Escherichia coli strain C1845 harboring the fimbrial F1845 adhesin can infect cultured human intestinal epithelial cells. The mechanism by which E. coli C1845 induces diarrheal illness remains unknown. This study investigated the injuries of cultured human intestinal cells promoted by E. coli C1845. Membrane-associated decay accelerating factor was identified as the intestinal receptor for the F1845 fimbrial adhesin of the E. coli C1845 strain by using purified F1845 adhesin, antibody directed against the F1845 adhesin, and monoclonal antibodies directed against the decay accelerating factor. Using monolayers of Caco-2 cells apically infected with E. coli C1845 and examined by scanning and transmission electron microscopy, we observed that strain C1845 induced injury to microvilli (MV) characterized by elongation and nucleation of the MV. We observed that infection of T84 and Caco-2 cells by E. coli C1845 was followed by disassembly of the actin network in the apical and basal cell domains. MV injury was differentiation related: E. coli C1845 promoted MV injury only when the cells were fully differentiated. The disassembly of the actin network occurred in poorly differentiated and fully differentiated Caco-2 cells but not in undifferentiated cells. Moreover, apical actin disassembly was observed in fully differentiated Caco-2 cells infected with the laboratory strain E. coli HB101(pSSS1) expressing the F1845 adhesin. In conclusion, E. coli C1845 promotes MV lesion in human epithelial intestinal cells, resulting from disassembly of the actin network.